2015
DOI: 10.1080/03081087.2015.1043855
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear *-Jordan derivations on von Neumann algebras

Abstract: Let A be a factor von Neumann algebra and φ be the * -Jordan2010 Mathematics Subject Classification. 46J10 , 47B48.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Note that, unlike von Neumann algebras which are always weakly closed, a standard operator algebra is not necessarily closed. The current work together with [7,[10][11][12][13][23][24][25][26] indicates that it is feasible to investigate * -Jordan-type derivations and * -Lie-type derivations on operator algebras under a unified framework-η- * -Jordan-type derivations. We have good reasons to believe that characterizing η- * -Jordan-type derivations on operator algebras is also of great interest.…”
Section: Related Topics For Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that, unlike von Neumann algebras which are always weakly closed, a standard operator algebra is not necessarily closed. The current work together with [7,[10][11][12][13][23][24][25][26] indicates that it is feasible to investigate * -Jordan-type derivations and * -Lie-type derivations on operator algebras under a unified framework-η- * -Jordan-type derivations. We have good reasons to believe that characterizing η- * -Jordan-type derivations on operator algebras is also of great interest.…”
Section: Related Topics For Future Researchmentioning
confidence: 99%
“…Let H be a complex Hilbert space and B(H) be the algebra of all bounded linear operators on H. Li et al in [10] showed that if [26]. Taghavi et al [23] and Zhang [25] independently investigate * -Jordan derivations on factor von Neumann algebras, respectively. It turns out that each nonlinear * -Jordan derivation on a factor von Neumann algebra is an additive * -derivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15], we showed that * -Jordan derivation map on every factor von Neumann algebra A ⊆ B(H) is additive * -derivation.…”
Section: Introductionmentioning
confidence: 99%
“…In [9] we showed that * -Jordan derivation map (i.e., φ(A ⋄ B) = φ(A) ⋄ B + A ⋄ φ(B)) on every factor von Neumann algebra A ⊆ B(H) is additive * -derivation. Moreover, in [7] we reduced the assumptions on the map φ.…”
mentioning
confidence: 99%